Evaluation of Garlic Genotypes for Yield and Yield Components in Islamabad, Pakistan Environment - Khan, H.; Hussain, M. M.; Jellani, G.; Tariq, S.; Naseeb, T.; Mahmood, S. (The Nucleus, 2018)
Seven different cultivars of garlic (Allium sativum L.) were evaluated for yield and yield parameters at the vegetable program (HRI), National Agricultural Research Council (NARC) Islamabad in 2014-15 and 2015-16.Yield parameters like survival %age, no of leaves/plant, plant height, no. of cloves/bulb, avg. bulb weight and fresh yield were recorded. In both years, it was observed that Cultivar “NARC-G1” gave the best survival (100%), minimum and wider leaves/plant (10), average plant height (38.2 cm), minimum cloves (8.3) per bulb and comparatively larger bulbs, maximum bulb weight (126.6 gm) and maximum fresh yield (25.6 t/ha), followed by Cultivar “ Italian”, which gave (22.4 t/ha), while Cultivar “Lehson Gulabi” was noted at the bottom and gave (15.2 t/ha).Hence, “NARC-G1” cultivar could be utilized in term of better yield and as well as industrial use for value addition purposes.